Exploring the pharmacological mechanism of calculus bovis in cerebral ischaemic stroke using a network pharmacology approach. (10th February 2022) - Du, Xin; Li, Changxiang; Zhang, Shuang; Sun, Chunyan; Zhang, Xiaole; Chen, Congai; Wang, Xueqian; Cheng, Fafeng; Wang, Qingguo
Abstract: Ethnopharmacological relevance: Calculus bovis is commonly used in traditional Chinese medicine for the treatment of cerebrovascular diseases given its roles in clearing away heat, detoxification and pain relief. Calculus bovis is used the treatment of cerebral ischaemia, liver and gallbladder diseases and various inflammatory conditions. However, the mechanism of action of calculus bovis in the treatment of ischaemic stroke is not well understood. Aim of the study: In this study, the anti-inflammatory, antioxidative and antiapoptotic effects of calculus bovis on neurovascular units were studied, and the mechanism of action of calculus bovis on neurovascular units was also discussed. Materials and methods: Neurons, astrocytes, and endothelial cells were used to construct models of brain neurovascular units in vitro. The oxygen–glucose deprivation/reoxygenation and glucose (OGD/R) model was used to assess the effects of in vitro cultured calculus bovis on inflammatory factors, oxidative stress, and apoptosis. ZO-1, Occludin, Claudin-5, HIF-1, VEGF, PI3K, Akt, Bax, Bcl-2, and Caspase-3 expression was detected. Results: In vitro cultured calculus bovis protects the blood-brain barrier; repairs tight junction proteins; increases ZO-1, Occludin and Claudin-5 protein expression; maintains TEER(transepithelial electrical resistance) values; repairs damaged endothelial cells; increases γ-GT activity; reduces LDH and inflammatory injury; and reduces TNF-α, LI-6, and IL-1β levels. In vitro cultured calculus bovis reduces oxidative stress damage and NO and improves SOD activity. In vitro cultured calculus bovis protects neurons through antiapoptotic activities, including reductions in the apoptotic proteins Bax and Caspase-3, increases in Bcl-2 protein expression, and protection of brain neurovascular units through the HIF/VEGF and PI3K/Akt signalling pathways. Conclusion: In summary, the protective effect of calculus bovis on neurovascular units is achieved through antioxidative, anti-inflammatory and antiapoptotic effects. The mechanism of action of in vitro cultured calculus bovis in ischaemic stroke involves multiple targets and signalling pathways. The PI3K/Akt, HIF-1α and VEGF pathways effectively protect neurovascular units in the brain. Graphical abstract: Image 1